Mathematical Modeling as an Educational Method of Synchronous Generator Operating Modes in a Diesel Power Plant; Procedia - Social and Behavioral Sciences; Vol. 206 : Linguistic and Cultural Studies: Traditions and Innovations, LKTI - Sipaylova N. Yu. Nadezhda Yurievna (2015, 2015)
Title screen